Resilience and identity of the Osage nation: A textual analysis of Killers of the Flower Moon - Hasyim, Fuad (NOTION: Journal of Linguistics, Literature, and Culture, 2025)
This study examines the resilience of the Osage Nation as portrayed in Killers of the Flower Moon, focusing on cultural persistence, adaptation, and resistance. Grounded in Antonio Gramsci’s theory of cultural hegemony, this research explores how dominant narratives shape public perceptions of Indigenous resilience and agency. This research systematically identifies and interprets recurring themes related to resilience by employing textual analysis. While existing literature on Native American resilience primarily explores broad themes, there is a notable gap in research that investigates the specific resilience strategies of distinct Native American groups, such as the Osage Nation. The findings reveal that cultural persistence ensures the continuity of traditions and values, adaptation enables survival in a changing sociopolitical landscape, and resistance plays a vital role in asserting Indigenous agency. Nonetheless, the study also highlights potential biases in the film’s portrayal, mainly focusing on victimization rather than active political and legal resistance. The research underscores the importance of analyzing cinematic representations critically, as they influence public perceptions and historical memory. Furthermore, this study highlights the limitations of fictionalized narratives as historical sources and calls for future research on the real-world impact of Indigenous representations in media on policy and cultural advocacy.